Global flyway evolution in red knots Calidris canutus and genetic evidence for a Nearctic refugium. Issue 7 (15th February 2022) - Conklin, Jesse R.; Verkuil, Yvonne I.; Battley, Phil F.; Hassell, Chris J.; ten Horn, Job; Johnson, James A.; Tomkovich, Pavel S.; Baker, Allan J.; Piersma, Theunis; Fontaine, Michaël C.
Abstract: Present‐day ecology and population structure are the legacies of past climate and habitat perturbations, and this is particularly true for species that are widely distributed at high latitudes. The red knot, Calidris canutus, is an arctic‐breeding, long‐distance migratory shorebird with six recognized subspecies defined by differences in morphology, migration behavior, and annual cycle phenology, in a global distribution thought to have arisen just since the last glacial maximum (LGM). We used nextRAD sequencing of 10, 881 single‐nucleotide polymorphisms (SNPs) to assess the neutral genetic structure and phylogeographic history of 172 red knots representing all known global breeding populations. Using population genetics approaches, including model‐based scenario‐testing in an approximate Bayesian computation (ABC) framework, we infer that red knots derive from two main lineages that diverged ca. 34, 000 years ago, and thus most probably persisted at the LGM in both Palearctic and Nearctic refugia, followed by at least two instances of secondary contact and admixture. Within two Beringian subspecies ( C . c . roselaari and rogersi ), we detected previously unknown genetic structure among sub‐populations sharing a migratory flyway, reflecting additional complexity in the phylogeographic history of the region. Conversely, we found very weak genetic differentiation between two Nearctic populations ( rufa and islandica ) with clearly divergent migratory phenotypes and little or no apparent contact throughout the annual cycle. Together, these results suggest that relative gene flow among migratory populations reflects a complex interplay of historical, geographical, and ecological factors.